Cystic Fibrosis Transmembrane Conductance Regulator Folding Mutations Reveal Differences in Corrector Efficacy Linked to Increases in Immature Cystic Fibrosis Transmembrane Conductance Regulator Expression - Peters, Kathryn W.; Gong, Xiaoyan; Frizzell, Raymond A. (Frontiers in Physiology, 2021)
Background: Most cystic fibrosis is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene that lead to protein misfolding and degradation by the ubiquitin–proteasome system. Previous studies demonstrated that PIAS4 facilitates the modification of wild-type (WT) and F508del CFTR by small ubiquitin-like modifier (SUMO)-1, enhancing CFTR biogenesis by slowing immature CFTR degradation and producing increased immature CFTR band B. Methods: We evaluated two correction strategies using misfolding mutants, including the common variant, F508del. We examined the effects on mutant expression of co-expression with PIAS4 (E3 SUMO ligase), and/or the corrector, C18. To study the impact of these correction conditions, we transfected CFBE410- cells, a bronchial epithelial cell line, with a CFTR mutant plus: (1) empty vector, (2) empty vector plus overnight 5 μM C18, (3) PIAS4, and (4) PIAS4 plus C18. We assessed expression at steady state by immunoblot of CFTR band B, and if present, band C, and the corresponding C:B band ratio. The large PIAS4-induced increase in band B expression allowed us to ask whether C18 could act on the now abundant immature protein to enhance correction above the control level, as reported by the C:B ratio. Results: The data fell into three mutant CFTR categories as follows: (1) intransigent: no observable band C under any condition (i.e., C:B = 0); (2) throughput responsive: a C:B ratio less than control, but suggesting that the increased band C resulted from PIAS4-induced increases in band B production; and (3) folding responsive: a C:B ratio greater than control, reflecting C18-induced folding greater than that expected from increased throughput due to the PIAS4-induced band B level. Conclusion: These results suggest that the immature forms of CFTR folding intermediates occupy different loci within the energetic/kinetic folding landscape of CFTR. The evaluation of their properties could assist in the development of correctors that can target the more difficult-to-fold mutant conformations that occupy different sites within the CFTR folding pathway.